2020
DOI: 10.3390/foods9050563
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Evaluative Label on Consumer Perception of Cheeses in Hungary

Abstract: Traditional strategies (such as education, economic incentives or prohibitions) targeted at altering dietary habits only influence health-conscious consumers. Less health-conscious consumers are less capable of self-regulatory behavior, therefore they are more likely to be influenced through perception. The present study aimed to examine how external cues such as labeling affect the consumer’s perception of foods. The paper includes a case study based on an experiment. In the experiment the same cheese was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…The risks include material products consumed, behavior and attitude of the food service establishment employees, and the environment (tangible feature at the time of purchase) in which the food is prepared and served (Goh et al., 2013 ). Therefore, the eating environment is a benchmark for establishing whether a food service outlet provides safe foods or not (Worsfold & Worsfold, 2008 ; Tóth & Bittsánszly, 2014 ; Szakály et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The risks include material products consumed, behavior and attitude of the food service establishment employees, and the environment (tangible feature at the time of purchase) in which the food is prepared and served (Goh et al., 2013 ). Therefore, the eating environment is a benchmark for establishing whether a food service outlet provides safe foods or not (Worsfold & Worsfold, 2008 ; Tóth & Bittsánszly, 2014 ; Szakály et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, such consumers may not read food labels [ 36 ], may be not interested in food safety issues [ 37 ], and may not be oriented toward any specific aspect of food products, including their health-promoting properties [ 38 ]. It may be assumed that they do not have any specific expectations associated with food products, as the major value of food for them is associated with satisfying their hunger, rather than palatability and pleasure of consumption, but this approach is rare [ 39 ]. It may result from the fact that they have neither positive nor negative expectations associated with food products, but they have neutral expectations associated with choosing minimally tolerable products as good enough for them [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It clearly evidenced that the indication of 'low in fat' or 'low salt content' had an impact on consumers' expectations and perceptions. An extensive review by Fernqvist and Ekelund (2014) concluded that health-related labels influenced product acceptance, so that the presence of this label information had a negative influence in the sensory consumeŕs perception, in an experiment conducted by Szakály et al (2020) on Trappista cheese from Hungary. Also, Barros et al (2016), found that consumers proposed health, sensory and economic conditioning when purchase fresh cheeses from Brazil with mentions about 'salt content' or 'probiotic microorganisms' on the label.…”
Section: Iii2 Current Degree Of Label Compliancementioning
confidence: 99%